Equine Coital Exanthema: new insights on the knowledge and leading perspectives for treatment and prevention - Vissani, Maria Aldana; Damiani, Armando Mario; Barrandeguy, Maria Edith (MDPI, 2021)
Equine coital exanthema (ECE) is a highly contagious, venereally-transmitted mucocutaneous disease, characterized by the formation of papules, vesicles, pustules and ulcers on the external genital organs of mares and stallions, and caused by equid alphaherpesvirus 3 (EHV-3). The infection is endemic worldwide and the virus is transmitted mainly through direct contact during sexual intercourse and by contaminated instruments during reproductive maneuvers in breeding facilities. The disease does not result in systemic illness, infertility or abortion, yet it does have a negative impact on the equine industry as it forces the temporary withdrawal of affected animals with the consequent disruption of mating activities in breeding facilities. The purpose of this review is to provide up-to-date relevant information on the knowledge of EHV-3 infection and to analyze new approaches on diagnostics, treatment and prevention in the interest of minimizing the negative consequences of ECE in light of the current situation of the equine industry.